Impact of hearing loss and vestibular decline on cognition in Alzheimer's disease: a prospective longitudinal study protocol (Gehoor, Evenwicht en Cognitie, GECkO). Issue 9 (17th September 2020) - Bosmans, Joyce; Jorissen, Cathérine; Cras, Patrick; Van Ombergen, Angelique; Engelborghs, Sebastiaan; Gilles, Annick; Princen, Eline; Moyaert, Julie; Mertens, Griet; Van Rompaey, Vincent
Abstract : Introduction: Dementia is a prevalent disease affecting a growing number of the ageing population. Alzheimer's disease (AD) is the most common cause of dementia. Previous research investigated the link between hearing loss and cognition, and the effect of vestibular dysfunction on cognition. Hearing loss and, to a lesser extent, vestibular decline both result in a decreasing cognitive function. However, their interaction should not be underestimated. The aim of this study is to assess the effect of hearing loss, vestibular decline and their interaction on cognition in people suffering from mild cognitive impairment (MCI) and dementia due to AD (ADD). Methods and analysis: We designed a prospective longitudinal study to assess the effect of hearing loss and vestibular decline on cognition. A total of 100 cognitively impaired elderly (between 55 and 84 years of age), consisting of 60 patients with MCI due to AD and 40 patients with ADD will be included. The control group will consist of individuals with preserved cognition group-matched based on age, hearing level and vestibular function. A comprehensive assessment is performed at baseline, 12-month and 24-month follow-ups. The primary outcome measure is the change in the Repeatable Battery for the Assessment of Neuropsychological Status adjusted for Hearing-impaired individuals total score, a cognitive test battery assessing different cognitive domains. Secondary outcome measures include additional neuropsychological assessments, cortical auditory-evoked potentials, and evaluation of general and disease-specific health-related quality of life. Variables include cognitive, audiological and vestibular evaluation. Variance analyses will assess the effect of hearing loss and vestibular decline on cognition. More precisely, the link between hearing loss and non-spatial cognitive functioning, the effect of vestibular decline on spatial cognition and the impact of both factors on the rate of conversion from MCI due to AD to ADD will be investigated. Ethics and dissemination: The study protocol was approved by the ethical committee of the Antwerp University Hospital on 4 February 2019 with protocol number B300201938949. The findings will be disseminated through peer-reviewed publications and conference presentations. Trial registration number: ClinicalTrials.gov Registry (NCT04385225 ).